PENGARUH JENIS DAN JUMLAH PENAMBAHAN GULA PADA KARAKTERISTIK WINE SALAK - Wayan Gunam, Ida Bagus; Wrasiati, Luh Putu; Setioko, Wito (Agrotekno, 2009)
The research was aimed to determine the effect of typeand concentration of sugar on the characteristics of producedsalacca wine and to determine the type and concentration ofsugar yielding salacca wines with the best characteristics andpreferred by panelists. Sensory test results showed that themost preferred salaca wine characteristics by panelists wasthose which produced with addition of 25% sucrose sugar(w/v), and the produced wine contained 14.81% of ethanol,2.66% of total sugar, 0.21% of total acid, pH 3.67, 10.5°Brixof total soluble solids, and methanol content was notdetected.